Storage of Verbal Associations Is Sufficient to Activate the Left Medial Temporal Lobe - Andrew R. Mayes; Patricia A. Gooding; Nicola M. Hunkin; Julia A. Nunn; Lloyd J. Gregory; Michael J. Brammer; Edward T. Bullmore; Vincent Giampietro; Rob Van Eijk; Amanda K. Nicholas; Steve C. R. Williams (Behavioural Neurology)
Neuroimaging studies have shown that memory encoding activates the medial temporal lobe (MTL). Many believe that these activations are related to novelty but it remains unproven which is critical - novelty detection or the rich associative encoding it triggers. We examined MTL activation during verbal associative encoding using functional magnetic resonance imaging. First, associative encoding activated left posterior MTL more than single word encoding even though novelty detection was matched, indicating not only that associative encoding activates the MTL particularly strongly, but also that activation does not require novelty detection. Moreover, it remains to be convincingly shown that novelty detection alone does produce such activation. Second, repetitive associative encoding produced less MTL activation than initial associative encoding, indicating that priming of associative information reduces MTL activation. Third, re-encoding familiar associations in a well-established way had a minimal effect on both memory and MTL activation, indicating that MTL activation reflects storage of associations, not merely their initial representation.